2017
DOI: 10.19082/3833
|View full text |Cite
|
Sign up to set email alerts
|

Levels of cytokines in the aqueous humor of eyes with primary open angle glaucoma, pseudoexfoliation glaucoma and cataract

Abstract: ObjectiveThe focus of this study aimed at measuring multiple inflammatory cytokines levels in the aqueous humor of patients with primary open angle glaucoma (POAG), pseudoexfoliation glaucoma (PEXG) and senile cataract.MethodsThis case control study was conducted at the Research Institute of Ophthalmology, Giza, Egypt in 2016. Aqueous humor (AH) samples were withdrawn from 50 patients (30 POAG, and 20 PEXG) and from 15 patients with senile cataract serving as controls. The levels of IL6, IL8, transforming grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 28 publications
2
32
1
3
Order By: Relevance
“… 10 , 11 , 18 However, in line with studies performed by others, 10 , 19 our results did not show any statistically significant difference in terms of AH Aβ 42 concentration between the glaucoma and control groups or with respect to other clinical parameters. Conversely, we found a significant increase of TP in the AH of glaucomatous patients, consistent with previous reports showing an increment of pro-inflammatory cytokine 20 23 and proteins related to the extracellular matrix remodeling 24 in the AH of subjects affected by glaucoma. Interestingly, our results indicate that this increase in TP was greater within the female group of glaucomatous patients, although the lower number of male patients could have biased these results (12 male vs. 20 female glaucomatous AH samples).…”
Section: Discussionsupporting
confidence: 93%
“… 10 , 11 , 18 However, in line with studies performed by others, 10 , 19 our results did not show any statistically significant difference in terms of AH Aβ 42 concentration between the glaucoma and control groups or with respect to other clinical parameters. Conversely, we found a significant increase of TP in the AH of glaucomatous patients, consistent with previous reports showing an increment of pro-inflammatory cytokine 20 23 and proteins related to the extracellular matrix remodeling 24 in the AH of subjects affected by glaucoma. Interestingly, our results indicate that this increase in TP was greater within the female group of glaucomatous patients, although the lower number of male patients could have biased these results (12 male vs. 20 female glaucomatous AH samples).…”
Section: Discussionsupporting
confidence: 93%
“…; Khalef et al. ; Kokubun et al. ) IL‐8 is a main chemoattractant for neutrophils which have been found to accumulate in the trabecular meshwork in POAG.…”
Section: Discussionmentioning
confidence: 99%
“…; Khalef et al. ) This discrepancy may have resulted from differences in laboratory techniques and specific patient groups. So far, to our knowledge, only sporadic studies are available on the effect of anti‐TNF medication in glaucoma, which shows an increase in fibrosis after surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that TGFβ-1, IL-8, and SAA have critical roles in IOP elevations in patients with POAG ( 20 ). Another group found the levels of IL-8, TGFβ-1, TNF-α, and SAA to be significantly increased in POAG and pseudoexfoliation glaucoma (PEXG) patients compared with controls, while levels of IL-6 were significantly decreased in both glaucoma groups compared with controls ( 41 ).…”
Section: Discussionmentioning
confidence: 99%